LEIOMYOMA OF THE VULVA - DR.K.LAVANYA; DR.S.M.PRIYADHARSHINI; DR.K.SARASWATHI (International Journal of Pharma and Bio Sciences, 2014)
38 years old multiparous women admitted with a swelling in the vulval region, which was asymptomatic except for the progressive increase in size over the past one and half years. A temptative diagnosis of bartholin`s cyst was made because of its location and proceeded with excision. The histopathology report was consistent with that of leiomyoma. This case is being presented for the rare occurrence of leiomyoma in the vulva.